Effects of acetylsalicylic acid and metamizol on hyaluronidase activity and sperm characteristics in rams - Tanyildizi, S; Bozkurt, T (Elsevier, 2003)
The effects of acetylsalicylic acid and metamizol on hyaluronidase activity of semen and sperm characteristics in rams were investigated. Acetylsalicylic acid and metamizol at the doses of 75 and 50 mg/kg were administered to the rams, respectively and then semen samples were taken at 1, 2, 4, 24, 48, 96, 120 and 144 h. The hyaluronidase activities of semen in rams treated with acetylsalicylic acid and metamizol were determined to increase significantly (P < 0.001) when compared with control groups at all times. Additionally, the spermatozoa motilities in both groups were measured to increase significantly (P < 0.05) when compared with control group. Furthermore, there were significant (P < 0.01, < 0.05) decreases in the sperm concentrations and semen volumes of rams treated with acetylsalicylic acid and metamizol at all times, respectively. In conclusion, although the use of acetylsalicylic acid and metamizol cause an increase in the hyaluronidase activities and spermatozoa motilities, these drugs decrease the sperm concentrations and semen volumes along 6 days. For these reason, the use of these drugs in breeding rams during ramming season is not suitable. (C) 2003 Elsevier Science B.V. All rights reserved.
Keywords: sheep-male reproduction; acetylsalicylic acid; metamizol; hyaluronidase; sperm